(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the clinical outcomes of patients who received bailout thrombectomy for primary percutaneous coronary intervention. Study Design: Observational / cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Cardiology, Bolan Medical Complex Hospital Quetta from July 2018 to December 2018. Materials and Methods: Two hundred patients of both genders undergoing primary percutaneous coronary intervention were analyzed in this study. All patients were divided into two groups. Group A comprised 100 patients and received PPCI with bailout thrombectomy and Group B comprised 100 patients and received primary percutaneous coronary intervention alone. Outcomes such as mortality, re-infarction, heart failure, cardiogenic shock, renal impairment, excess bleeding, post procedure stroke and hospital stay were examined and compare between both groups. Results: In Group A, there were 53% males and 47% females with mean age56.45±10.88 years. In Group B 55% were males and 45% were females with mean age 58.35±9.23 years. In Groups A there were more diabetic patients 45% than Group B 32% (p-value 0.005), Group B had more smokers 60%. There was a significant difference between group A and B regarding family history of coronary artery disease 35% vs 20% (p=0.003). In Group A, 3% patients were died and in Group B 2% patients were died with no significant difference. Group A patients had more renal impairment 9% vs 5% and stroke 3% vs 1% than Group B. Hospital stay was high in Group A patients 7.12±2.05 vs 5.34±1.02 days. Conclusion: Patients received bailout thrombectomy for percutaneous coronary intervention had high rate of comorbidities. There was no significant difference in term of mortality between both groups. However, patients with bailout thrombectomy had more renal impairment and post-procedure stroke